(untitled) (LEGAL DIALOGICA, 2025)
This research aims to identify, understand, and analyze the forms and stages of legal protection for children as victims of violence by teachers in schools based on Indonesian laws and regulations. The research method used is normative research, a legal research method that utilizes secondary legal materials or library research that focuses on examining legal norms as the primary basis, including relevant regulations, books, articles, journals, research results, papers, and other relevant sources relevant to the issues discussed. The results of this study indicate that problems that commonly occur in education are not only socioeconomic but have also penetrated the legal realm, as evidenced by the numerous cases arising in schools related to violence perpetrated by teachers against their students. Teachers, who should be at the forefront of protecting children in schools, are actually doing the opposite. The research question is how legal protection is provided for child victims of violence by teachers in the school environment, and what the stages in the protection process are. The recommendations in this study include increased supervision in the school environment, legal counseling for educators, and strengthening the role of child protection agencies. Furthermore, strong coordination between relevant institutions is needed, capacity building for educators through anti-violence training, and the establishment of an effective reporting and monitoring system in schools Abstrak: Penelitian ini bertujuan untuk mengetahui, memahami, dan menganalisis bentuk dan tahapan perlindungan hukum anak sebagai korban kekerasan guru di lingkungan sekolah berdasarkan peraturan perundang-undangan di Indonesia. Metode penelitian yang digunakan adalah penelitian normatif, yakni suatu metode penelitian hukum yang menggunakan bahan hukum sekunder atau merupakan penelitian keputakaan yang berfokus mengkaji norma hukum sebagai dasar utama yang meliputi peraturan yang relevan, buku-buku, artikel, jurnal, hasil penelitian, makalah, dan sebagiannya yang relevan permasalahan yang akan dibahas. Hasil penelitian ini menunjukkan bahwa masalah yang biasanya terjadi di dunia pendidikan tidak hanya berpusar dibidang sosial ekonomi saja, tetapi juga sudah merambah dalam ranah hukum, terlihat dari banyaknya kasus yang timbul di lingkungan sekolah yang bersangkutan dengan kekerasan yang dilakukan oleh oknum guru pada anak didiknya. Guru yang semestinya menjadi garda terdepan dalam melindungi anak di sekolah justru melakukan hal yang sebaliknya. Permasalahan dalam penelitian ini adalah bagaimana bentuk perlindungan hukum terhadap anak korban tindak pidana kekerasan oleh guru di lingkungan sekolah serta bagaimana tahapan dalam proses perlindungannya. Rekomendasi dalam penelitian ini adalah diharapkan adanya peningkatan pengawasan di lingkungan sekolah, penyuluhan hukum kepada tenaga pendidik, serta penguatan peran lembaga perlindungan anak. Serta perlunya koordinasi yang kuat antar lembaga terkait, peningkatan kapasitas tenaga pendidik melalui pelatihan anti-kekerasan, serta pembentukan sistem pelaporan dan pengawasan yang efektif di sekolah